Material outcome of early versus late termination of pregnancy among pregnant mothers with prenatal diagnosis of lethal fetal anomalies: a retrospective review - S.L., Yong; Abdulwahab, Dalia F; Ismail, Hamizah; Ismail, Rozihan; Awang, Mokhtar; Abdullah, Suhaiza (2012)
Objective: To compare the maternal morbidities between early (< 22 weeks gestation) and late (≥ 22 weeks gestation) termination of pregnancy (TOP) among pregnant mothers with prenatal diagnosis of lethal fetal anomalies.